The Impact of Digital Economic Transformation on Green Economic Growth in Indonesia - Dasa febriyanti; Sri Haryani; Awaluddin (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
Digital economic transformation has a significant impact on green economic growth in Indonesia. This article highlights the important role of digital technology and green business practices in increasing efficiency, productivity, and environmental awareness in various economic sectors. Digital economic transformation refers to the use of digital technology in various aspects of economic life, such as e-commerce, fintech, and business digitalization. Meanwhile, a green economy refers to sustainable and environmentally friendly development. The positive impacts of this transformation include reducing the carbon footprint, creating new jobs, and diversifying the economy. However, there are still challenges that need to be overcome, such as the digital divide and limited adoption of environmentally friendly business practices. To overcome this challenge, supportive policies, investment in digital infrastructure, and increased awareness of the importance of sustainable development for green economic growth in Indonesia are needed.